2015
DOI: 10.3329/brj.v19i1.25223
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of Producer and Consumer Preference Models for Rice Varieties in Bangladesh

Abstract: Rice production depends on both producers' and consumers' preference. The consumption of rice depends on consumers' taste and habits. The objectives of this study were to develop and validate mathematical models for producers', consumers' and producers-cum-consumers' preference to rice varieties and to evaluate the factors affecting both producers' and producer-cum-consumers' decision on varieties for rice cultivation and can provide an indication of the factors affecting consumers' preferences to rice varieti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…We review global, regional and national studies on consumer preferences for rice conducted in selected countries in Southeast Asia (SEA) and South Asia (SA) throughout three decades (Unnevehr, 1986;several chapters in Unnevehr et al, 1992a;Juliano and Villareal, 1993;Rachmat et al, 2006;Calingacion et al, 2014;Hossain et al, 2015). Different sampling schemes and methods in data collection were used in these studies.…”
Section: Historical Trends In Consumer Preferencesmentioning
confidence: 99%
See 1 more Smart Citation
“…We review global, regional and national studies on consumer preferences for rice conducted in selected countries in Southeast Asia (SEA) and South Asia (SA) throughout three decades (Unnevehr, 1986;several chapters in Unnevehr et al, 1992a;Juliano and Villareal, 1993;Rachmat et al, 2006;Calingacion et al, 2014;Hossain et al, 2015). Different sampling schemes and methods in data collection were used in these studies.…”
Section: Historical Trends In Consumer Preferencesmentioning
confidence: 99%
“…This rice type, which is consumed as water rice or as plain rice, makes them feel full which allows them to endure long working hours on the farm. In Bangladesh, preferences have shifted in the last twenty years from short-size-medium-shaped to finer, slender grains (Juliano and Villareal, 1993;Calingacion et al, 2014;Hossain et al, 2015).…”
Section: Historical Trends In Consumer Preferencesmentioning
confidence: 99%
“…For instance, producers and producer-cum-consumers preferred rice varieties for higher yield, whereas pure consumers preferred varieties on the basis of its tastiness and fineness. The specific grain quality characteristics such as whiteness, broken, shape, amylose (%), aroma, cooking quality, hardness, and chalkiness largely influenced the preferences of both consumers and producers (Hossain et al, 2015). Another study found that 96% of the consumers in Bangladesh bought parboiled rice from the market because of consumption habit (57%), not sticky (15.7%), easily digestible (15.2%), tasty (13.2%), durability (12.2%), and expansion ratio (3.8%) (Jaim and Hossain, 2009).…”
Section: Consumers' Preferencesmentioning
confidence: 99%
“…In Bangladesh, different rice varieties respond differently to different environmental conditions with varying yields and production risk (Hossain et al, 1990;Joshi and Bauer, 2006;Hossain and Barker, 2007;Rahman et al, 2020;Kabir et al, 2021) and to mitigate the risks associated, farmers' adaptation to the changing conditions is made through the adoption of improved varieties with new traits or combination of traits (Kabir et al, 2015;Siddique et al, 2018;Karmakar et al, 2021;Rahman et al, 2023). Thus, rice breeding programs in Bangladesh are designed to develop new rice varieties with traits like high yield, short duration, resistance to pests and diseases, and tolerance to other biotic and abiotic stresses to curtail farmers' adoption lag (Choudhury et al, 1992;Jaim and Hossain, 2009;BRRI, 2015;Hossain et al, 2015;Kabir et al, 2015;Tiongco and Hossain, 2015). However, genetic improvements for these specific traits alone may not be sufficient for new rice varieties to be adopted by different farmer groups as factors like gender may have considerable weight in determining if a variety will be adopted (Weltzien et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation